2021
DOI: 10.1089/neu.2021.0148
|View full text |Cite
|
Sign up to set email alerts
|

Tracking White and Gray Matter Degeneration along the Spinal Cord Axis in Degenerative Cervical Myelopathy

Abstract: This study aims to determine tissue-specific neurodegeneration across the spinal cord in patients with mildmoderate degenerative cervical myelopathy (DCM). Twenty-four mild-moderate DCM and 24 healthy subjects were recruited. In patients, a T2-weighted scan was acquired at the compression site, whereas in all participants a T2*-weighted and diffusion-weighted scan was acquired at the cervical level (C2-C3) and in the lumbar enlargement (i.e., rostral and caudal to the site of compression). We quantified intram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 38 publications
5
34
0
Order By: Relevance
“…Some also found deficits in RD and MTR pointing to the demyelination [8,28,82] and AD alteration due to axonal injury as the primary alteration at MCL [8]. Rostral secondary changes in DCM patients presented as lower FA and higher diffusivity measures in dorsal columns and lateral corticospinal tracts and changes in 1 H-MRS ratios at C2/3 level point to remote Wallerian degeneration above the compression level [8,32,39,40,42,43,75,103,104]. Subtle remote changes at C2/3 level between NMDC and HC were then revealed by the multi-compartment Ball-and-Sticks diffusion model, 1 H-MRS, and MTR [8,28,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some also found deficits in RD and MTR pointing to the demyelination [8,28,82] and AD alteration due to axonal injury as the primary alteration at MCL [8]. Rostral secondary changes in DCM patients presented as lower FA and higher diffusivity measures in dorsal columns and lateral corticospinal tracts and changes in 1 H-MRS ratios at C2/3 level point to remote Wallerian degeneration above the compression level [8,32,39,40,42,43,75,103,104]. Subtle remote changes at C2/3 level between NMDC and HC were then revealed by the multi-compartment Ball-and-Sticks diffusion model, 1 H-MRS, and MTR [8,28,32].…”
Section: Discussionmentioning
confidence: 99%
“…SC volumetry adds to the compression metrics at MCL when assessing changes above and below the compression levels. So far, studies demonstrated gradual reduction of SC, WM and GM volumes at C2/3 above the compression level in DCM and NMDC relative to HC and each other (Figure 2) [8,32,[39][40][41][42][43], pointing to more severe Wallerian neurodegeneration and atrophy in DCM than NMDC [8,41] with similar changes in DCM also caudally at T11-L1 level [43]. However, morphometric and volumetric metrics might suffer from inter-subject variability due to anatomical and biological factors such as age, sex, height or weight, which showed significant correlations in healthy subjects and patients with SC compression [2,[44][45][46].…”
Section: Structural Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, researchers have relied on conventional cervical spine MRI to monitor and determine spinal cord structural changes in DCM patients, e.g., high signal intensity on T2-weighted MR ( 8 , 9 ). Its utility remains controversial as the information obtained from the spinal cord area is limited, i.e., the small cross-sectional area ( 10 12 ). Therefore, researchers set their sights on resting-state functional MRI for exploring brain alterations in patients with DCM ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%